A kinetic-based simulation model of palm kernel shell steam gasification in a circulating fluidized bed using Aspen PlusÂ®: A case study - Hussain, M. (Taylor and Francis Ltd., 2018)
A detailed simulation model for hydrogen production using catalytic steam gasification of palm kernel shell in an atmospheric dual fluidized bed gasifier using an Aspen PlusÂ® simulator is developed. The catalytic adsorbent-based steam gasification of palm kernel shell is studied in a pilot scale dual fluidized bed reactor using coal bottom ash as a catalyst for hydrogen and syngas production. The use of a catalyst along with the adsorbent improved tar cracking and enhanced the hydrogen content of syngas. The effect of temperature and the steamâbiomass ratio on hydrogen yield, syngas composition and lower and higher heating values was studied. An increase in steamâbiomass ratio enhanced the hydrogen content from 60 to 72 mol. The maximum value of hydrogen production, i.e. 72 vol was achieved at a steamâbiomass ratio of 1.7. The use of adsorbent and coal bottom ash had a significant effect on hydrogen and syngas yield. A maximum of 80.1 vol hydrogen was achieved at a temperature of 650 Â°C with a 1.25 steamâbiomass ratio and 0.07 wt coal bottom ash. Â© 2018 Informa UK Limited, trading as Taylor & Francis Group